Доклад Международного комитета по контролю над наркотиками за 2015 год - United Nations Office on Drugs; Crime (United Nations, 2016)
This annual report prepared by The Board provides a comprehensive account of the global drug situation, analyses trends in drug abuse and drug trafficking and suggests necessary remedial action. Divided into four parts, it covers the following topics: drugs and corruption, functioning of the international drug control system, analysis of the world situation and finally, a set of recommendations to Governments, the United Nations and other relevant international and regional organizations. A set of Annexes follows as well.